2014
DOI: 10.1001/jama.2014.15825
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Screening for Coronary Artery Disease Using CT Angiography on Mortality and Cardiac Events in High-Risk Patients With Diabetes

Abstract: clinicaltrials.gov Identifier: NCT00488033.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
214
1
7

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 334 publications
(226 citation statements)
references
References 18 publications
4
214
1
7
Order By: Relevance
“…CCTA may be a good modality to triage diabetes individuals who are at high risk of future CVD events due to the direct visualization of subclinical atherosclerosis including non-calcified plaque [14,16]. A recent prospective randomized trial in 900 asymptomatic diabetes individuals demonstrated that CCTA reduced risk of major adverse cardiovascular events by 20% compared to standard diabetes care; however, this failed to achieve statistical significance (HR 0.80, 95% CI 0.49e1.32, p ¼ 0.38) [46].…”
Section: Discussionmentioning
confidence: 99%
“…CCTA may be a good modality to triage diabetes individuals who are at high risk of future CVD events due to the direct visualization of subclinical atherosclerosis including non-calcified plaque [14,16]. A recent prospective randomized trial in 900 asymptomatic diabetes individuals demonstrated that CCTA reduced risk of major adverse cardiovascular events by 20% compared to standard diabetes care; however, this failed to achieve statistical significance (HR 0.80, 95% CI 0.49e1.32, p ¼ 0.38) [46].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, annual event rates in both the control and intervention groups were low (<2%), and outcomes (death, MI, or unstable angina) did not differ significantly between the CCTA and no CCTA groups after a mean of 4 years of follow-up. 74 At present, these findings do not support CCTA screening for risk assessment of individuals without chest pain.…”
Section: Disclosuresmentioning
confidence: 69%
“…Similarly, the Screening For Asymptomatic Obstructive Coronary Artery Disease Among High-Risk Diabetic Patients Using CT Angiography, Following Core 64 (FACTOR 64) trial randomised patients with diabetes and no symptoms of CAD to screening coronary computed tomography angiography (CCTA) or usual care. 5 After a mean follow-up of 4.0 years there was no significant difference in event rates between the screened and unscreened groups (6.2 versus 7.6 %). Randomisation to CCTA resulted in only 36 (8 %) coronary angiographies and 26 (5.8 %) coronary revascularisations.…”
Section: Decision To Perform Revascularisationmentioning
confidence: 75%